Financial Management of State Universities as Public Service Agency in Supporting The Development of Human Resources and Facilities (Study at the Faculty of Languages and Arts, Universitas Negeri Manado) - Raranta, Regina; Sendouw, Recky H. E.; Kantohe, Meidy (Technium Social Sciences Journal, 2023)
Public service agencies are basically a tool to improve the performance of public services for the development of human resources as well as infrastructure facilities through the implementation of financial management based on results, professionalism, accountability, and transparency. The aim of this research is to describe and analyze the financial management of state universities as public service agencies (BLU) in supporting the development of human resources and infrastructure (Study at the Faculty of Languages and Arts (FBS) Universitas Negeri Manado). The research method used is a qualitative method with a purposive sampling technique in determining informants. The research results show that, among other things, 1) Financial management planning for state universities that implement public service bodies must be able to accommodate the interests of both parties (central government and state universities); 2) There needs to be transparency in financial management. In terms of what and for what the institution’s finances need to be recorded and accounted for, accompanied by proof of its use; 3) Financial planning needs to be done every year by taking into account the needs that occur in the next year. Planning must be designed to be close to reality through comprehensive planning. Apart from that, the implementation of management of state assets must be directed at management that provides academic and economic benefits through the tridharma of higher education; 4) Important things to pay attention to when preparing a budget plan: a. Inventory the plans to be implemented b. Develop a plan based on the priority scale for implementation c. Determine the work program and program details d. Determine the need for implementation of program details e. Calculating the funds needed f. Determine the source of funds to finance the plan.